KEY CONTENT AND STRUCTURAL COMPONENTS OF CORPORATE CULTURE - Filipova, Milena (Revista Inclusiones, 2021)
Corporate culture forms a part of the image of an organization. It is developed by the people within the organization and has a strong influence on them. At the same time, it affects the outside audiences, too. The culture influences at the level of emotions, implies though its irrational elements, attracts to its values. Corporate culture influences personnel’s behaviour in different aspects of work process, such as the communications with customers, the compliance with standards at work, the openness to innovations and novelties, the responsibility and sense of duty. The main objective of this article is to study the content and structural components of corporate culture. The main results expected are identified key content and structural components of corporate culture. The main research methods used in the article are content analysis, method of comparison, intuitive and systematic approach, method of analysis and synthesis.